Zoning the villages at flood risk in the Varkesh-Chai drainage basin by GIS and HEC - RAS software and HEC- GEO - RAS extension - Asdollah hejazi; fatemeh khodaie geshlag; leila khodaie geshlag (تحقیقات کاربردی علوم جغرافیایی)
Varkesh-Chai River with approximately 69 kilometer and north-south trend, in one of the main and permanent rivers of Tabriz city, That 10 villages with worn out texture have established in its main bed. Field studies show that, villages’development has been without knowing the rules governing hydraulic behavior, prediction of river hydrological behavior, and no respecting the main bed of river, it has been conserved to the agricultural land or garden. Lack of knowledge and attention to the above-mentioned cases and river bed manipulation has increased the vulnerability of villages, agricultural land or other human facilities of the flood risk in the catchment area. Therefore, it is necessary to study the areas potential to the flood occurrence and to prepare floodplain maps in district. In present study, flood levels were determined along the main river, during the return periods of 25 and 50 years.  For this purpose, geography information systems (GIS) and HEC_RAS model and HEC_GEO_RASextension were usedto simulate earth geometry, river plans, left and right rivers shores, and flow rate obtained then, the villages exposed to flood with these return peaks were identified and then, hydraulic behavior of the river was simulated. Finally, solution to reduce the damages caused by flood along the main river were identified.